CYBER SPACE PROTECTION MODEL CYBERSEC - Tkach, Yuliia (Ukrainian Information Security Research Journal, 2023)
The article proposes a cyberspace protection model CyberSec, which is focused on performing the function of "cyber protection". This model is functional, consists of five stages, combines a number of methods and models, is cyclical, and therefore allows you to create a selfconfiguring protection system in cyberspace. At the first stage of "Intelligence and Detection" is a description of the security environment, ie a threat model is formed, which is a complete list of all possible threats that exist or may arise in this situation, then assumptions are made about the attacker, and therefore the violator model is formed. The second stage of "Armament" is the choice of means of protection and construction of a system of cyberspace protection (SSC). To do this, it is necessary to develop an approach that will make the optimal (which provides the best (optimal) protection) choice of the functional profile of cybersecurity, while spending less time than usual. Carrying out control of the system (cyberspace) is the third stage of "Control". To do this, the analysis of the main tasks of information security, determines the real level of interest of security entities in compliance with all requirements for the security of each of the properties of information (for example, sufficient, low, unacceptable). At the fourth stage of "Counteraction" to the construction of secure cyberspace, the evaluation of the effectiveness of the proposed SZK is performed. In the fifth stage of "Active Counteraction", normative documents are prepared, corporations are informed about cybersecurity incidents, active counteraction is carried out at the state level, ie countermeasures are applied. The CyberSec cyberspace protection model allows you to build a secure cyberspace in practice for both an individual corporation and the state as a whole.